A Shape Memory High‐Voltage Supercapacitor with Asymmetric Organic Electrolytes for Driving an Integrated NO2 Gas Sensor. (12th April 2019) - Song, Changhoon; Yun, Junyeong; Lee, Hanchan; Park, Heun; Jeong, Yu Ra; Lee, Geumbee; Kim, Min Su; Ha, Jeong Sook
Abstract: A high‐voltage supercapacitor with shape memory for driving an integrated NO2 gas sensor is fabricated using a Norland Optical Adhesive 63 polymer substrate, which can recover the original shape after deformation by short‐time heating. The supercapacitor consists of multiwalled carbon nanotube electrodes and organic electrolyte. By using organic electrolyte consisting of adiponitrile, acetonitrile, and dimethyl carbonate in an optimized volume ratio of 1:1:1, a high operation voltage of 2 V is obtained. Furthermore, asymmetric electrolytes with different redox additives of hydroquinone and 1, 4‐dihydroxyanthraquinone to the anode and cathode, respectively, enhance both capacitance and energy density by ≈40 times compared to those of supercapacitor without redox additives. The fabricated supercapacitor on the Norland Optical Adhesive 63 polymer substrate retains 95.8% of its initial capacitance after 1000 repetitive bending cycles at a bending radius of 3.8 mm. Furthermore, the folded supercapacitor recovers its shape upon heating at 70 °C for 20 s. In addition, 90% of the initial capacitance is retained even after the 20th shape recovery from folding. The fabricated supercapacitor is used to drive integrated NO2 gas sensor on the same Norland Optical Adhesive 63 substrate attached onto skin to detect NO2 gas, regardless of deformation due to elbow movement. Abstract : The fabrication of a shape memory high‐voltage supercapacitor with asymmetric nonaqueous electrolytes including redox additives for driving an integrated NO2 gas sensor is demonstrated. Using an asymmetric organic electrolyte greatly enhances the performance of the supercapacitor. Furthermore, the supercapacitor and NO2 gas sensor can be driven after several shape recoveries, successfully.